The gender aspect of the struggle for the Moscow throne of the end of the 17th century in the Russian historiography - Медведська Л. (Київський національний університет імені Тараса Шевченка, 2009)
The picularities of the political confrontation of Natalia Naryshkina and tsarevna Sophia are analysed on the basis of the works of the Russian historians.

Особливості політичного протистояння Наталії Наришкіної та царівни Софії аналізуються на основі праць російських істориків.
Гендерний аспект боротьби за московський престол кінця XVII століття у російській історіографії